Digital elite and traditional politicians - V. A. Perepelkin; O. V. Kryshtanovskaya (Цифровая социология)
The article examines the transformation of legitimation of political power amid digitalisation and competition between traditional political elite and digital elite representatives. This process is linked to the growing networked nature of contemporary society and increasing role of social media platforms in daily life. Based on empirical analysis of social media accounts of politicians and influencers, the study identifies differences in online engagement effectiveness, communication strategies, and nature of published content. Online activity of both groups and engagement of audience into communication are analysed. The findings show that the digital elite representatives significantly outperform the politicians in audience size and loyalty. To consider the obtained indicators, qualitative content analysis methods are applied, and a typology of posts by digital and political elites is developed. The limited effectiveness of the politicians’ online engagement is attributed to their reliance on formal, structurally one-sided communication practices. In their public activity, they mainly focus on strengthening systemic legitimacy, which reduces their effectiveness on social networks. By contrast, the digital elite agents employ more personalised, emotional, and interactive ways of presenting information, generating audience interest and boosting popularity. Thus, the key difference between the two elites is that public communications of the official avatars are primarily aimed at building trust in government, rather than gaining personal popularity for its actors. The article stresses the need to adapt state communication to the new realities of digital competition for citizens’ attention and trust.